Cancer of the Larynx: A Brief Overview with Case Studies - Bulbulia, Bashir Ahmed; Ahmed, M R (British Journal of Healthcare and Medical Research, 2024)
Laryngeal cancer (LC) is globally a common malignancy affecting the the head and neck (HN) region. It occurs in the aero digestive tract and is the second most common tumour affecting the (HN) area. Squamous cell carcinoma (SCC) make up to 96% of LC. The surgical removal of LC remains an important modality of treatment. Therapeutically chemo-radiation therapy is incorporated in early and late stages of the disease and has been a game changer in preserving laryngeal organ function. Advances in endoscopic laser technology with trans-oral resection (TOR) of many cancers reduces morbidity and preserves laryngeal function.Treatment modalities include immunotherapy (biological) and targetting cancer cells (target therapy) to prevent cancer cell multiplication. Genetic biomarkers are unravelling newer information of the disease (LC). Risk modification factors for LC are cessation of smoking and discouraging the use of alcohol products.